Les risques conchylicoles en Baie de Quiberon. Première partie : le risque de mortalité virale du naissain d’huître creuse Crassostra gigas. Rapport final du projet Risco 2010-2013 ... - Mazurie, Joseph; Stanisiere, Jean-Yves; Langlade, Aime; Bouget, Jean-Francois; Dumas, Franck; Treguier, Cathy; Leclerc, Emilie; Ravaud, Emilie; Quinsat, Kevin; Gabellec, Raoul; Retho, Michael; Cochet, Helene; et al. (Ifremer, 2013)
This study (“Risco”), implicating both industry, socio-economic experts and biologists, was funded by the Regional Council of Brittany, for 3 years (2010-2013), to investigate upon the origin of oysters (Crassostrea gigas) mortalities in the bay of Quiberon (South Brittany, France). Specific mortalities of adult oysters were recorded in this bay in 2006, whereas mortalities of one year old spat were observed since in 2008 in this bay as at a national scale. The experimental protocol in 2010, including a monthly survey of oyster batches at 15 experimental stations, allowed to assess the risk for one-year oysters, due to viral disease. A clear spatial distribution of this risk was evidenced, with a western area spared from contamination and mortality, and a central and north-east sector strongly affected. The virus analysis clearly demonstrate the responsibility of the OsHV-1 virus in the mortalities. The oysters on the bottom with a lower growth appear less sensitive to the viral disease than the surelevated ... : L’étude « Risco », labellisée Pôle Mer et financée par la Région Bretagne, mobilise à la fois des socio-économistes, des biologistes et des professionnels. Elle vise à comprendre et gérer les facteurs de mortalités massives d’huîtres creuses (Crassostrea gigas) enregistrées par les concessionnaires de baie de Quiberon (France, 56), à partir de 2006 sur les huîtres adultes et 2008 sur le naissain. Le protocole engagé en 2010, avec un volet expérimental basé sur le suivi mensuel de lots d’huîtres en 15 stations et des analyses pathologiques, a permis d’éclairer notamment le risque épizootique sur le naissain. Une spatialisation très marquée de ce risque a été mise en évidence, avec une zone à l’ouest relativement épargnée et une zone au centre et à l’est très affectée. Les analyses virales mettent clairement en évidence la responsabilité du virus OsHV-1 dans ces mortalités. Les huîtres élevées au sol, moins poussantes, seraient aussi moins sensibles à la mortalité virale que les huîtres élevées en ...